Clinically Indicated Renal Biopsy in Type 2 Diabetes Mellitus – It Is Not Always Nondiabetic Kidney Disease - Ramprasath Rajan; S. Murugesh Anand; Ramasubramanian Viswanathan; Kannan Bhaba Velu; P. K. Senthil Kumar; P. Shankar (Indian Journal of Kidney Diseases)
Introduction: The manifestations of diabetes mellitus in the kidney can be in the form of diabetic nephropathy (DN), nondiabetic kidney disease (NDKD), and DN with overlapping NDKD features. We conducted this study to examine the incidence of DN in kidney biopsies done in diabetic patients to diagnose NDKD. Materials and Methods: This study was an ambispective study done in a tertiary medical college hospital. Data were collected from all type 2 diabetic patients who underwent kidney biopsy. Clinical, histopathological, and laboratory parameters were compared between the three groups (DN, NDKD, and DN with overlapping NDKD features). Results: Of the 82 diabetic patients who underwent kidney biopsy, the incidence of DN, NDKD, and NDKD with DN was 30.2%, 39.6%, and 30.2%, respectively. Rapidly progressive renal failure was the common indication for the biopsy. In patients with only DN, the common indication for biopsy was rapid worsening of proteinuria. Acute tubular injury and infection-related glomerulonephritis were the common NDKD in patients with overlapping DN. Diabetic retinopathy was noted in 63.2% of the patients with DN. 77.7% of the patients with macrovascular complications had only DN. On histological analysis, the patients with only DN had higher grades of tubulointerstitial and vascular changes which could explain their atypical presentation. Conclusion: In this study, with clinically indicated biopsies, the incidence of patients with only DN is significant (30.2%). Scrutiny of histopathological findings such as a correlation between glomerular and tubulointerstitial lesions will broaden the understanding of varied clinical presentations of DN which will help in clinical decision-making, individualize interventions, and optimize the care of these patients.